Development of Schiff bases from Amikacin: Synthesis, Antibacterial, Anti-urease Activities and Molecular Docking Studies - Anwar, Shabana; Khan, Mohsin A.; Ahmed, Irshad; Pervaiz, Irfan; Shah, Hamid Saeed (Letters in Drug Design & Discovery, 2020)
Background: The use of antibiotics has compromised due to the appearance of multidrug- resistant strains and decreased susceptibility of strains to antibiotics. Antibiotic resistance has become a worldwide threat as well as Helicobacter pylori induced gastric cancer is a major problem nowadays. Therefore, it is the need of time to synthesize potent anti-urease motifs. Introduction: Schiff bases represent a large class of biologically active compounds that exhibited a broad spectrum of biological activities. Amikacin is an important drug used against multidrugresistant species of microbes. Therefore, imine derivatives of amikacin may help to reduce the resistance of microbes and to treat the Helicobacter pylori induced stomach problems by inhibiting the Helicobacter Pylori Urease enzyme. Methods: Schiff bases of amikacin were synthesized and screened for in-vitro antibacterial assay performed by well diffusion method against Bacillus megaterium (Bm), Bacillus subtilis (Bs), Stenotrophomonas maltophilia (Sm), Staphylococcus aureus (Sa), Micrococcus luteus (Ml), Serratia marcescens (S. mar), Escherichia coli (E. coli) and anti-urease activity was performed by Indophenol method. Structures confirmed by IR, 1HNMR and 13CNMR spectroscopy. Results: Compounds showed varying degrees of antibacterial effects. Schiff bases A2 and A8 exhibited potent urease inhibition activity with Ki values 0.2754 and 0.2908 μM, respectively and their binding affinity was calculated as greater than the standard drug. Conclusion: Derivatives of amikacin with aromatic rings were more active antibacterials than those with an aliphatic side chain. The potent anti-urease activity has been recorded for compounds A2 and A8. Therefore, they may serve as lead compounds in the discovery of Helicobacter pylori Urease inhibitors.
Keywords: Schiff bases